Innovative Multi-Color LED HPL Lamps for Improved Efficiency in Floating Lift Net Fishing - Jailani, Abdul Qadir; Suharyanto, Suharyanto; Ruchimat, Toni (Graha Primera Saintifika, 2025)
This research focuses on the design and fabrication of a high-power LED (HPL) light that integrates red, green, and blue LEDs for underwater lighting, commonly known as